Zinc Phosphate and Resin Cements Provide Similar Bonding of Cast Metal Post to Dentin - Ferreira, Carolina J.; Benetti, Paula; Nicolodi, Karen; da Rocha, Larissa S.; De Carli, João P. (Current Drug Targets - Inflammation & Allergy, 2003)
Background: Cast metal posts-and-core are frequently used to retain restorations to extensively destroyed teeth. However, the influence of different cements on the posts bond strength to dentin remains unclear. Objective: to evaluate the effect of different cements on the bond strength of cast metal posts and dentin. Methods: Forty roots (14 mm length) of extracted human teeth were endodontically treated and prepared. Impressions of each root canal were taken to obtain customized cast metal posts. The roots were randomly divided into 4 groups (n=10): (1) ZP: zinc phosphate cement (non adhesive); (2) ARC_Sin: Single Bond adhesive and RelyX ARC; (3) ARC_Sco: Scotchbond adhesive and RelyX ARC; (4) U200: RelyX U200. After cementation, the samples were cross-sectioned to obtain specimens of 1mm thickness. Push-out test was performed applying a compressive load (0.5 mm/min) to the center of the metal post until failure. Bond strength was calculated based on the diameter of the root canal and the thickness of each specimen. Data were analyzed using ANOVA and Tukey (α=0.05). The fracture mode was analyzed. Results: Bond strength values were statistically similar between the groups (p>0.05). The fracture analysis showed the prevalence of mixed fractures (cement partially attached to the dentin and/or post). Experimental groups showed inexpressive amount of adhesive fractures (complete detachment of the cement from dentin and/or post). The ARC_Sco and U200 groups presented higher prevalence of dentin cohesive fracture. Conclusion: Bonding had no influence on the immediate bond strength between cast metal posts and root canal dentin.
Keywords: dentine